2019
DOI: 10.1128/mcb.00576-18
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing Replication from Barriers: Mechanistic Insights from Single-Molecule Studies

Abstract: To prevent replication failure due to fork barriers, several mechanisms have evolved to restart arrested forks independent of the origin of replication. Our understanding of these mechanisms that underlie replication reactivation has been aided through unique dynamic perspectives offered by single-molecule techniques. These techniques, such as optical tweezers, magnetic tweezers, and fluorescencebased methods, allow researchers to monitor the unwinding of DNA by helicase, nucleotide incorporation during polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…These results suggested a potential replication recovery pathway in which the inactivation of a replisome by a DNA lesion might also be capable of resuming replication from a stalled RNAP. Recently, Sun et al used an optical tweezer to examine this possibility and showed that T7 helicase associates with nonreplicating DNAP, jointly unwinding DNA at a fork …”
Section: Optical Tweezersmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested a potential replication recovery pathway in which the inactivation of a replisome by a DNA lesion might also be capable of resuming replication from a stalled RNAP. Recently, Sun et al used an optical tweezer to examine this possibility and showed that T7 helicase associates with nonreplicating DNAP, jointly unwinding DNA at a fork …”
Section: Optical Tweezersmentioning
confidence: 99%
“…Recently, Sun et al used an optical tweezer to examine this possibility and showed that T7 helicase associates with nonreplicating DNAP, jointly unwinding DNA at a fork. 43 By using an optical tweezer coupled to confocal microscopy, Bi et al found that two BLM helicases carrying out the unwinding of two forked DNA substrates oligomerize upon head-on collision leading to fork convergence. 44 Oligomerization is mediated by the helicase and RNaseD C-terminal (HRDC) domain of BLM such that it tightly bridges two newly generated ssDNA strands from unwinding.…”
Section: ■ Optical Tweezersmentioning
confidence: 99%
“…Compared with ensemble studies, single-molecule approaches have shown great advantages in measurements of molecular heterogeneity, distributions in molecular behaviors, and real-time dynamics of single biomolecules (Cordes et al 2015 ; Cuculis and Schroeder 2017 ; Leake 2013 ; Sun 2019 ; Sun and Wang 2016 ). A wide variety of fluorescence spectroscopy-based (DNA curtains and fluorescence resonance energy transfer) and force spectroscopy-based (magnetic tweezers, optical tweezers, and atomic force microscopy) single-molecule techniques have been used to investigate different aspects of Cas9 proteins (Cuculis and Schroeder 2017 ; Globyte et al 2018 ; Singh and Ha 2018 ; Whinn et al 2019 ).…”
Section: Single-molecule Techniques For Cas9 Studiesmentioning
confidence: 99%
“…This high-powered approach, and other innovative strategies in SM experimentation, ushered in a new era for mechanistic studies of DNA helicases. Some of the important and diverse innovations in SM studies of DNA helicases are discussed below from a historical perspective, but due to the broad scope of the field readers are encouraged to consult some timely reviews [207][208][209].…”
Section: Single-molecule Studies Of Helicase-catalyzed Dna Unwindingmentioning
confidence: 99%